Non-noble metal loaded nitrogen-doped mesoporous carbon catalyst for hydrogenation synthesis of gamma-valerolactone from levulinic acid and preparation method of non-noble metal loaded nitrogen-doped mesoporous carbon catalyst

Through a non-precious metal-supported nitrogen-doped mesoporous carbon catalyst wrapped with an amorphous carbon layer, the problems of complex process and poor stability of existing catalysts in the preparation of γ-valerolactone during the hydrogenation of levulinic acid are solved, and high efficiency and stability are achieved catalytic effect.

CN119456014APending Publication Date: 2025-02-18XIANGTAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411778288.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-25
Filing Date
2024-12-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the process of hydrogenation of levulinic acid, existing catalysts have problems such as complex process, poor stability, low selectivity and active metal leaching.

Method used

A non-precious metal-supported nitrogen-doped mesoporous carbon catalyst is used to form a stable carbon layer through low-temperature hydrothermal treatment to inhibit the agglomeration and leaching of active metal nanoparticles.

Benefits of technology

It has achieved efficient conversion of levulinic acid under mild conditions, with γ-valerolactone selectivity close to 100%, and the catalyst cycle stability is good. After 10 repetitions, it still maintains LA conversion rate of more than 90% and GVL selectivity of more than 98% after 10 repetitions. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456014A_ABST
    Figure CN119456014A_ABST
Patent Text Reader

Abstract

The invention relates to a non-noble metal-loaded nitrogen-doped mesoporous carbon catalyst for synthesizing gamma-valerolactone through hydrogenation of levulinic acid and a preparation method of the non-noble metal-loaded nitrogen-doped mesoporous carbon catalyst. The non-noble metal is selected from one of Co, Fe, Ni and Zr and is wrapped in a carbon layer in a nano-particle form. The preparation method comprises the following steps: pyrolyzing melamine to obtain a graphite-phase C3N4 carrier; mixing C3N4 with glucose and a metal nitrate aqueous solution, and performing low-temperature hydrothermal treatment; and carrying out carbon thermal reduction on the centrifugally separated solid in a nitrogen atmosphere to obtain the catalyst. The catalyst provided by the invention is simple in preparation process and high in yield, and gamma-valerolactone can be prepared by efficiently catalyzing levulinic acid hydrogenation under mild conditions. According to the method, hydrogen is used as a hydrogen source, levulinic acid, a solvent and a catalyst are put into a closed container, the reaction is performed for 3 hours at the temperature of 180 DEG C under the hydrogen pressure of less than 2 MPa, the complete conversion of levulinic acid can be realized, the yield of gamma-valerolactone is as high as 99.7%, no metal is separated out, and the conversion rate of levulinic acid is still kept above 90% after the catalyst centrifugally separated after the reaction is recycled for 10 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of heterogeneous catalysis, and specifically relates to a non-precious metal-loaded nitrogen-doped mesoporous carbon catalyst wrapped in an amorphous carbon layer and a method for efficiently catalyzing the hydrogenation of levulinic acid to prepare gamma-valerolactone. Background Art

[0002] Biomass is the only carbon-neutral raw material in nature and can be used as the best choice to replace traditional fossil energy in the context of carbon neutrality and energy shortage. γ-Valerolactone (GVL), as the most critical derivative of the biomass platform molecule levulinic acid (LA), has been widely used in other high value-added chemicals such as gasoline additives, resin solvents, plasticizers and chemical intermediates. Obviously, the preparation of GVL based on LA catalytic hydrogenation ensures the sustainable supply of renewable fuels and chemicals, but the poor catalytic activity and stability of most catalysts and cost issues prevent large-scale application. Therefore, the key to preparing GVL from LA is to develop a catalyst with high catalytic activity.

[0003] In the prior art, noble metal catalysts such as Ru show excellent activity in LA hydrogenation, but such catalysts are scarce and expensive and are not suitable for mass production. For example, patent CN 111841611B discloses a method for preparing GVL by hydrogenation of LA using Ru single-atom catalysts. The GVL yield and selectivity of the reaction for 2h at 100°C and 2MPa hydrogen pressure are both above 99%, but it involves complex processes such as preparation of metal precursors assisted by gap polyacids, ion exchange, high-temperature pyrolysis and etching to remove templates. The literature (ACS Sust. Chem. Eng., 2016, 4: 2939-2950) reports the hydrogenation effect of LA on three catalysts (Ru / C, Ru / γ-Al2O3 and Ru / TiO2). The GVL yields of 6h at 90°C and 4.5MPa hydrogen pressure are 81.3%, 9.6% and 14.0%, respectively, confirming the advantages of porous carbon carriers in LA hydrogenation, but a large number of by-products are produced during the reaction. The above catalysts all show Ru aggregation and leaching when using water as solvent, which reduces the stability of the catalyst. Patent CN 108409692B discloses a Ru-loaded sulfur-doped carbon catalyst and a method for preparing GVL by hydrogenation of LA. The Ru-loaded catalyst is obtained by sulfur-doping carbon nanotubes by vapor deposition and then undergoing a homogeneous oxidation process. The method adds LA and a catalyst to a solvent and uses hydrogen as a reducing agent to reduce LA to GVL. The reaction is carried out at 120°C and 3MPa hydrogen pressure for 6h to achieve complete conversion of LA and a GVL selectivity of 99.2%, but when the reaction time is shortened to 2h, the LA conversion rate drops to 70.5%.

[0004] Compared with precious metal catalysts, non-precious metals are low-cost and abundant in resources, but it is an indisputable fact that their activity is weaker than that of precious metal catalysts. Most non-precious metal catalysts need relatively harsh reaction conditions (high temperature, high pressure and long reaction time) to show good hydrogenation effects under mild conditions. The literature (Green Chem., 2012, 14: 1064.) reported that Cu / ZrO2 and Cu / Al2O3 can achieve complete conversion of LA and 90% GVL selectivity at 200°C and 5MPa hydrogen pressure, but this type of catalyst is easy to deactivate, metal particles are prone to leaching or agglomeration during circulation, and even produce secondary contamination of metal ions. A large number of studies have confirmed that porous carbon supports, especially nitrogen-doped carbon supports, can make active metals have higher dispersion and stability, and promote the preparation of GVL from LA under relatively mild conditions. Non-precious metal-supported carbon catalysts such as Zn, Cu, Co, Ni, Fe, and Zr have been reported in the application of LA hydrogenation to GVL and have excellent activity. The literature (Fuel Process. Technol., 2023, 240: 107559.) reports a solvent evaporation-induced self-assembled ordered mesoporous carbon-loaded Ni-Zn catalyst, which can obtain a 93% GVL yield by reacting for 1.5 hours at 180°C and 2MPa hydrogen pressure. Patent CN 114308094B discloses a method for Co single atom-loaded nitrogen-doped mesoporous carbon fiber, which can achieve complete LA conversion by reacting for 5 hours at 200°C and a hydrogen pressure of 4.5MPa, and the GVL selectivity reaches 95%. After 5 cycles, the GVL yield remains above 80%. Patent CN 113546664B discloses a fish scale biochar-loaded Co catalyst and a method for preparing GVL by LA hydrogenation. This type of catalyst uses fish scale as a raw material to obtain a precursor through a hydrothermal reaction, and uses ethylenediamine to chelate metal cobalt to obtain a complex, which is then mixed with melamine and ground and then pyrolyzed at high temperature. The LA conversion rate is as high as 99%, and the GVL yield is close to 100%. Obviously, the non-precious metal catalyst based on nitrogen-doped carbon carrier shows outstanding catalytic efficiency. Nitrogen doping can significantly increase the electronic state density of the inert carbon carrier, and the strong interaction between nitrogen atoms and active metal electrons greatly activates the metal catalytic ability. Considering that water is inevitably generated as a byproduct during the catalytic hydrogenation of LA to prepare GVL, the aqueous solution is prone to leaching active metals. Therefore, it is necessary to develop a type of catalyst that is resistant to metal precipitation while ensuring the high activity of the catalyst.

[0005] In summary, non-precious metal-supported nitrogen-doped carbon catalysts have great potential in the hydrogenation of LA to produce GVL. The preparation process of existing catalysts is relatively complicated, with high cost and poor stability. In particular, most catalysts also have problems such as high reaction temperature, high hydrogen pressure and long reaction time. In particular, the structure of the catalyst carrier has an important influence on the efficient hydrogenation of LA to produce GVL. For example, 1) the mesoporous structure of the carrier can promote the adsorption and diffusion of the reaction substrate, accelerate the contact between the reaction substrate and the active metal, and thus improve the conversion efficiency. 2) The nitrogen coordination in the carrier can effectively anchor the active metal, and the amorphous carbon layer can make the active metal less likely to aggregate and leach, thereby improving the stability of the catalyst. Summary of the invention

[0006] The purpose of the present invention is to provide a non-precious metal supported nitrogen-doped mesoporous carbon (M-NCG) catalyst wrapped in an amorphous carbon layer and a method for efficiently catalyzing LA hydrogenation to GVL, so as to solve the problems of complex catalyst process, poor stability, low GVL selectivity, active metal leaching, etc. mentioned in the background technology. The non-precious metal M of the catalyst is selected from one of Fe, Co, Ni, and Zr; NCG represents a nitrogen-doped mesoporous carbon carrier.

[0007] A method for preparing a non-noble metal-loaded nitrogen-doped mesoporous carbon catalyst wrapped by an amorphous carbon layer comprises the following steps:

[0008] 1) pyrolyzing melamine in a tubular furnace under a nitrogen atmosphere to obtain a graphite phase C3N4 carrier;

[0009] 2) Add the C3N4 obtained in the above step to an aqueous solution of glucose and non-precious metal nitrate hydrate, stir thoroughly, and then place in a polytetrafluoroethylene-lined hydrothermal reactor for low-temperature hydrothermal treatment to obtain a precursor wrapped in an amorphous carbon layer; the non-precious metal is selected from one of Fe, Co, Ni, and Zr.

[0010] 3) The solid obtained by the hydrothermal reaction in the above step is centrifuged, filtered, washed, dried, and carbon thermally reduced under a nitrogen atmosphere to obtain a non-precious metal-loaded nitrogen-doped mesoporous carbon catalyst wrapped in an amorphous carbon layer.

[0011] As a preferred embodiment, the melamine thermal decomposition temperature in step 1) is 450-600° C., preferably 550° C.; the reaction time is 1-6 hours, preferably 2 hours.

[0012] As a preferred embodiment, the mass ratio of glucose to C3N4 in step 2) is 1:(0.2-1), and the mass ratio of nitrate hydrate to C3N4 is 1:1. The stirring temperature of the aqueous solution is room temperature, and the stirring time is 0.5-2h; the hydrothermal reaction temperature is 120-180°C, preferably 170°C; the hydrothermal reaction time is 6-36h, preferably 24h.

[0013] As a preferred embodiment, in the step 3), the carbon thermal reduction temperature of the catalyst precursor in a nitrogen atmosphere in a tubular furnace is 500-800° C., and the reaction time is 0.5-4 h.

[0014] The present invention also discloses a method for preparing γ-valerolactone by hydrogenating levulinic acid. The non-precious metal-loaded nitrogen-doped mesoporous carbon catalyst wrapped by the amorphous carbon layer prepared by the above steps can efficiently convert LA under mild conditions and show better GVL selectivity. More importantly, this type of catalyst has extremely high cyclic stability, and still maintains excellent catalytic activity after 10 repetitions, with an LA conversion rate of up to 90% and a GVL selectivity of more than 98%.

[0015] The specific method is: a certain amount of the above-synthesized catalyst, LA and solvent are stirred and mixed in a high-pressure reactor, hydrogen is filled three times to replace the air in the reactor, and then the hydrogen valve is closed, the reaction temperature and hydrogen pressure are set, and the LA conversion rate and GVL yield are tracked by gas chromatography.

[0016] In the above method, the reaction solvent is one of 1,4-dioxane, ethanol, methanol and isopropanol, preferably 1,4-dioxane; the mass ratio of levulinic acid to the catalyst in the reaction system is (3-20):1.

[0017] In the above method, the catalytic reaction temperature is 140-200°C, more preferably 180°C;

[0018] In the above method, the reaction time is 1 to 10 hours, more preferably 3 hours;

[0019] In the above method, the hydrogen pressure is 1-2 MPa, more preferably 1.8 MPa.

[0020] Compared with the prior art, the technical features and effects of the present invention are as follows:

[0021] 1) The present invention uses low-temperature hydrothermal to wrap an amorphous carbon layer on the outside of the precursor, and finally forms a stable carbon layer on the outside of the catalyst to effectively inhibit the agglomeration and leaching of active metal nanoparticles, thereby improving the reaction activity and catalyst stability.

[0022] 2) The catalyst provided by the present invention has a simple preparation process and low cost, and exhibits excellent activity in the hydrogenation of LA to GVL, with both the LA conversion rate and the GVL selectivity approaching 100%. In particular, there is no metal leaching during the reaction process, the LA conversion rate after 10 reuses is higher than 90%, and the GVL selectivity of the optimal catalyst remains above 98%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a transmission electron micrograph of the catalyst described in Example 1.

[0024] Figure 2 This is the pore size distribution diagram of the catalyst described in Example 1.

[0025] Figure 3 This is the nitrogen element X-ray photoelectron spectrum of the catalyst described in Example 1.

[0026] Figure 4 This is a graph showing the recycling performance of the catalyst described in Example 1. DETAILED DESCRIPTION

[0027] In order to further disclose but not limit the present invention, the present invention is further described below in conjunction with specific embodiments:

[0028] Embodiment 1-4:

[0029] Melamine was pyrolyzed at 550℃ for 4h (heating rate 5℃ / min) in a tubular furnace with nitrogen, and the graphite phase C3N4 yellow powder was ground. Take an appropriate amount of C3N4 powder and grind it with nitrate hydrate (Co, Ni, Fe, Zr) respectively, add it to 60mL glucose aqueous solution and stir for 30min. The mixed solution was transferred to a polytetrafluoroethylene-lined reactor for hydrothermal treatment at 170℃ for 24h, centrifuged to obtain a brown solid, dried at 80℃, pyrolyzed at 600℃ in a nitrogen atmosphere for 2h (heating rate 4℃ / min), and ground after cooling to obtain a non-precious metal-loaded nitrogen-doped carbon catalyst coated with an amorphous carbon layer, which were marked as Co-NCG-600, Ni-NCG-600, Fe-NCG-600, and Zr-NCG-600, respectively, representing Example 1, Example 2, Example 3 and Example 4.

[0030] The preparation parameters of the Co-NCG-600 catalyst in Example 1 are: C3N4: cobalt nitrate: glucose mass ratio = 0.6:0.6:1;

[0031] The preparation parameters of the Ni-NCG-600 catalyst described in Example 2 are: C3N4: nickel nitrate: glucose mass ratio = 0.6:0.6:1;

[0032] The preparation parameters of the Fe-NCG-600 catalyst described in Example 3 are: C3N4: ferric nitrate: glucose mass ratio = 0.4:0.4:1;

[0033] The preparation parameters of the Zr-NCG-600 catalyst described in Example 4 are: mass ratio of C3N4: zirconium nitrate: glucose = 0.4:0.4:1.

[0034] The structure of the Co-NCG-600 catalyst described in Example 1 was characterized. Figure 1It can be seen that the catalyst morphology is rich in metal nanoparticles coated with amorphous carbon layers; the nitrogen adsorption isotherm shows that the pore size of the catalyst is rich in mesoporous and macroporous structures, such as Figure 2 As shown. Figure 3 It can be seen that the catalyst surface is rich in pyridinic nitrogen and pyrrolic nitrogen structures, and the catalytic graphitization effect of non-precious metals during high-temperature pyrolysis makes its surface contain some graphitic nitrogen structures.

[0035] The catalyst obtained in Example 1-4 was applied to the selective hydrogenation of LA to synthesize GVL. The specific reaction steps were as follows: 0.05 g of the above four catalysts were respectively placed in a 50 mL polytetrafluoroethylene-lined reactor, and 0.5 g of LA and 20 mL of 1,4-dioxane were added. After sealing, the air was replaced by three hydrogen purges, the hydrogen pressure was adjusted to 1.8 MPa, the reaction temperature was set to 180 ° C, and the reaction was stirred magnetically at a speed of 1000 rpm for 3 hours. After the reaction was completed, the mixture was cooled to room temperature and samples were taken for gas chromatography analysis. The results showed that the above catalysts had excellent performance in the LA hydrogenation process. The LA conversion rates of Co-NCG-600, Ni-NCG-600, Fe-NCG-600 and Zr-NCG-600 catalysts were all over 90%, and the GVL yields were 99.7%, 93.2%, 84.2% and 81.5%, respectively. The test results are listed in Table 1, and serial numbers 1 to 4 represent Example 1, Example 2, Example 3 and Example 4, respectively.

[0036] Embodiment 5-7:

[0037] Weigh 0.05g of Co-NCG-600 catalyst in Example 1 and place it in a 50mL polytetrafluoroethylene-lined reactor, weigh 0.5g of LA and 20mL of 1,4-dioxane and add them to the reactor. After sealing, the air in the reactor was replaced by three hydrogen purges, the hydrogen pressure was adjusted to 1.8MPa, and the reaction temperature was set to 140℃, 160℃ or 200℃, respectively, and the catalyst performance was evaluated by magnetic stirring at 1000rpm for 3h. After the reaction was completed, it was naturally cooled to room temperature and sampled for gas chromatography analysis. The results showed that the performance of Co-NCG-600 catalyst during LA hydrogenation was greatly affected by the reaction temperature. At 140℃, the LA conversion rate dropped to 80.4%. The test results are listed in Table 1. The serial numbers are 5 to 7, representing Example 5, Example 6 and Example 7, respectively.

[0038] Embodiment 8-10:

[0039] Weigh 0.05g of Co-NCG-600 catalyst in Example 1 and place it in a 50mL polytetrafluoroethylene-lined reactor, weigh 0.5g of LA and 20mL of 1,4-dioxane and add them to the reactor. After sealing, the air in the reactor was replaced by three hydrogen purges, the reaction temperature was set to 180°C, hydrogen was introduced to make its pressure constant to 1.4MPa, 1.6MPa or 2.0MPa, and the catalyst performance was evaluated by magnetic stirring at 1000rpm for 3h. After the reaction was completed, it was naturally cooled to room temperature and sampled for gas chromatography analysis. The results showed that the performance of Co-NCG-600 catalyst during LA hydrogenation was greatly affected by hydrogen pressure. At 1.4MPa, the LA conversion rate dropped to 84.5%. The test results are listed in Table 1. The serial numbers are 8 to 10, representing Example 8, Example 9 and Example 10, respectively.

[0040] Table 1 Test and evaluation results of Examples 1-10

[0041]

[0042] Embodiment 11-13:

[0043] Weigh an appropriate amount of C3N4 powder in Example 1 and grind it with cobalt nitrate hydrate, add it to 60mL glucose solution and stir for 30min, the mass ratio of C3N4: cobalt nitrate: glucose = 0.6:0.6:1. The mixture solution was transferred into a polytetrafluoroethylene-lined reactor for hydrothermal treatment at 170°C for 24h, cooled to room temperature after the reaction, centrifuged to obtain a brown solid, dried at 80°C in vacuum, and pyrolyzed in a nitrogen atmosphere for 2h (heating rate 4°C / min), the pyrolysis temperature was 500°C, 700°C or 800°C, respectively, and ground to obtain a non-precious metal-loaded nitrogen-doped carbon catalyst coated with an amorphous carbon layer, and the above catalysts were recorded as Co-NCG-500, Co-NCG-700, and Co-NCG-800, respectively.

[0044] Weigh 0.05g of the above three catalysts respectively and place them in a 50mL polytetrafluoroethylene-lined reactor, weigh 0.5g of LA and 20mL of 1,4-dioxane and add them to the reactor. After sealing, the air in the reactor is replaced by three hydrogen purges, the hydrogen pressure is adjusted to 1.8MPa and the reaction temperature is set to 180°C, and the catalyst performance is evaluated by magnetic stirring at a speed of 1000rpm for 3h. After the reaction is completed, it is naturally cooled to room temperature and samples are taken for gas chromatography analysis. The results show that the pyrolysis temperature has a great influence on the catalyst performance. The test results are listed in Table 2. The serial numbers 11 to 13 represent Example 11, Example 12 and Example 13, respectively.

[0045] Examples 14-16

[0046] Weigh an appropriate amount of C3N4 powder in Example 1, grind it with cobalt nitrate hydrate, add it to 60mL glucose solution and stir for 30min, keeping the mass ratio of C3N4: cobalt nitrate: glucose = 0.6: 0.6: 1. The above mixture solution was transferred to a polytetrafluoroethylene-lined reactor for hydrothermal treatment for 24h, and the hydrothermal reaction temperature was set to 140°C, 160°C or 180°C, respectively. After natural cooling, centrifugal filtration was performed to obtain a brown solid, which was dried at 80°C and pyrolyzed at 600°C in a nitrogen atmosphere for 2h (heating rate 4°C / min). After cooling, grinding was performed to obtain amorphous carbon layer-coated non-precious metal-loaded nitrogen-doped carbon catalysts, which were marked as Co-NCG-600-140, Co-NCG-600-160, and Co-NCG-600-180, respectively.

[0047] Weigh 0.05g of the above three catalysts respectively and place them in a 50mL polytetrafluoroethylene-lined reactor, weigh 0.5g of LA and 20mL of 1,4-dioxane and add them to the reactor. After sealing, the air in the reactor is replaced by three hydrogen purges, the reaction temperature is set to 180°C, hydrogen is introduced to make its pressure constant to 1.8MPa, and the reaction is stirred magnetically at a speed of 1000rpm for 3h. After the reaction is completed, it is naturally cooled to room temperature and samples are taken for gas chromatography analysis. The results show that the hydrothermal reaction temperature of the precursor has a great influence on the LA hydrogenation performance of the subsequent catalyst. The test results are listed in Table 2. The serial numbers 14 to 16 represent Example 14, Example 15 and Example 16, respectively.

[0048] Embodiment 17

[0049] Weigh an appropriate amount of C3N4 powder in Example 1, grind it with cobalt nitrate hydrate, add it to 60mL aqueous solution and stir for 30min, keeping the mass ratio of C3N4: cobalt nitrate = 0.6:0.6. The above mixture solution was transferred to a polytetrafluoroethylene-lined reactor for hydrothermal treatment at 170°C for 24h, and naturally cooled to room temperature after the reaction was completed. The brown solid was obtained by centrifugal filtration, dried at 80°C, and pyrolyzed at 600°C in a nitrogen atmosphere for 2h (heating rate 4°C / min), and ground after cooling to obtain a non-precious metal-loaded nitrogen-doped carbon catalyst coated with an amorphous carbon layer, marked as Co-NC-600.

[0050] Weigh 0.05g of the above catalyst Co-NC-600 into a 50mL polytetrafluoroethylene-lined reactor, weigh 0.5g of LA and 20mL of 1,4-dioxane and add them to the reactor. After sealing, the air in the reactor was replaced by hydrogen purge three times, the hydrogen pressure was adjusted to 1.8MPa and the reaction temperature was set to 180°C, and the reaction was stirred magnetically at 1000rpm for 3h. After the reaction was completed, it was naturally cooled to room temperature and sampled for gas chromatography analysis. The test results are listed in Table 2, No. 17, which represents implementation 17.

[0051] Embodiment 18

[0052] Weigh an appropriate amount of C3N4 powder and nickel nitrate hydrate in Example 1 and grind them thoroughly, add them to 60 mL of glucose solution and stir for 30 min, keeping the mass ratio of C3N4: nickel nitrate: glucose = 0.6:0.6:1. The above mixture solution was transferred into a polytetrafluoroethylene-lined reactor for hydrothermal treatment at 170°C for 24 h, and centrifuged and filtered to obtain a brown solid after cooling. After drying at 80°C, pyrolysis was performed at 700°C in a nitrogen atmosphere for 2 h (heating rate 4°C / min), and then naturally cooled to room temperature and ground to obtain a non-precious metal-loaded nitrogen-doped carbon catalyst coated with an amorphous carbon layer, labeled Ni-NCG-700.

[0053] Weigh 0.05g of the above catalyst Ni-NCG-700 into a 50mL polytetrafluoroethylene-lined reactor, weigh 0.5g of LA and 20mL of 1,4-dioxane and add them to the reactor. After sealing, the air in the reactor was replaced by hydrogen purge three times, the hydrogen pressure was adjusted to 1.8MPa and the reaction temperature was set to 180°C, and the reaction was stirred magnetically at a speed of 1000rpm for 3h. After the reaction was completed, it was naturally cooled to room temperature and sampled for gas chromatography analysis. The test results are listed in Table 2, serial number 18, which represents Example 18.

[0054] Examples 19-20

[0055] Weigh an appropriate amount of C3N4 powder in Example 1 and grind it with nitrate hydrate (Fe, Zr) respectively, add it to 60mL glucose aqueous solution and stir for 30min, keeping the mass ratio of C3N4: nitrate: glucose = 0.4:0.4:1. The above mixture solution is transferred into a polytetrafluoroethylene-lined reactor for hydrothermal carbonization at 170°C for 24h, and naturally cooled to room temperature after the reaction. The brown solid is obtained by centrifugal filtration, dried at 80°C, pyrolyzed at 800°C in a nitrogen atmosphere for 2h (heating rate 4°C / min), and naturally cooled to room temperature. After grinding, amorphous carbon layer-coated non-precious metal-loaded nitrogen-doped carbon catalysts are obtained. The above catalysts are marked as Fe-NCG-800 and Zr-NCG-800, respectively.

[0056] Weigh 0.05g of the above catalysts Fe-NCG-800 and Zr-NCG-800 respectively and place them in a 50mL polytetrafluoroethylene-lined reactor, weigh 0.5g of LA and 20mL of 1,4-dioxane and add them to the reactor. After sealing, the air in the reactor is replaced by three hydrogen purges, the hydrogen pressure is adjusted to 1.8MPa and the reaction temperature is set to 200°C, and the catalyst performance is evaluated by magnetic stirring at a speed of 1000rpm for 3h. After the reaction is completed, it is naturally cooled to room temperature and samples are taken for gas chromatography analysis. The test results are listed in Table 2. Serial numbers 19 to 20 represent Example 19 and Example 20, respectively.

[0057] Table 2 Test evaluation results of Examples 11-20

[0058]

[0059] Taking the optimal catalyst Co-NCG-600 in Example 1 as an example, its cyclic stability of catalyzing LA hydrogenation to prepare GVL under mild conditions was determined.

[0060] After the initial reaction for 3 hours, the catalyst was recovered, washed with deionized water and ethanol, and placed in a drying oven at 80°C for drying. The catalyst cycle stability test was then carried out directly. The catalytic reaction operating parameters were as described in Example 1. After each cycle test, the liquid phase product was detected and analyzed. The cycle results are shown in Table 3.

[0061] Table 3 Cyclic stability evaluation results of LA hydrogenation to GVL catalyzed by Co-NCG-600

[0062]

[0063] As shown in Table 3, the best catalyst (Co-NCG-600) among the series of amorphous carbon layer-wrapped non-precious metal-loaded nitrogen-doped mesoporous carbon catalysts provided by the present invention still maintains high catalytic activity after 10 cycles, the LA conversion rate is still over 90%, and the GVL selectivity is stable at over 98%. The specific effects are shown in Figure 4 . This is attributed to the fact that the amorphous carbon layer in the catalyst structure can effectively inhibit the agglomeration and leaching of metal nanoparticles, the number of active sites is not lost during circulation, and the mesoporous structure of the catalyst allows the substrate to be quickly adsorbed near the active sites. The non-precious metal-loaded nitrogen-doped mesoporous carbon catalyst wrapped in an amorphous carbon layer provided by the present invention has a simple preparation process and low cost, and has great application potential in the preparation of γ-valerolactone by hydrogenation of levulinic acid.

[0064] The specific preferred implementation methods of the above cases further explain the present invention in detail. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. The above preferred implementation cases are only for illustrating the preparation method of the non-precious metal-loaded nitrogen-doped mesoporous carbon catalyst wrapped in an amorphous carbon layer provided by the present invention and a typical example of its LA hydrogenation to GVL reaction. In addition, the present application can also have many other implementation methods, and any technical solution formed by equivalent replacement or equivalent transformation should be deemed to be within the scope of protection of the present invention.

Claims

1. A non-noble metal-supported nitrogen-doped mesoporous carbon catalyst for hydrogenating levulinic acid to synthesize γ-valerolactone and a preparation method thereof, characterized in that: The non-precious metal in the catalyst is wrapped in the amorphous carbon layer in the form of nanoparticles, and the non-precious metal is selected from one of Fe, Co, Ni, and Zr; the non-precious metal nanoparticle size in the catalyst is 10 to 40 nm, the nitrogen doping mass concentration is 2 to 8%, and the mesopore size is 7 to 50 nm.

2. A method for preparing a catalyst as claimed in claim 1, characterized in that: The following steps are involved: 1) Pyrolyzing melamine to obtain a graphite phase C3N4 carrier; 2) adding the C3N4 obtained in the above step to an aqueous solution of glucose and metal nitrate hydrate, stirring thoroughly, placing the mixture in a polytetrafluoroethylene-lined hydrothermal reactor for low-temperature hydrothermal treatment, and obtaining a precursor wrapped in an amorphous carbon layer; 3) The solid obtained by the hydrothermal reaction in the above step is centrifuged and dried, and then carbon thermally reduced under a nitrogen atmosphere to obtain a non-precious metal-loaded nitrogen-doped mesoporous carbon catalyst (M-NCG) wrapped in an amorphous carbon layer, where M represents a non-precious metal and NCG represents a nitrogen-doped mesoporous carbon carrier.

3. The method for preparing a catalyst according to claim 2, characterized in that: The melamine thermal decomposition temperature in step 1 is 450-600° C., preferably 550° C.; the reaction time is 1-6 hours, preferably 2 hours.

4. The method for preparing a catalyst according to claim 2, characterized in that: The mass ratio of glucose to C3N4 in step 2 is 1:(0.2-1), and the mass ratio of nitrate hydrate to C3N4 is 1:1; the stirring temperature of the mixed aqueous solution is room temperature, and the stirring time is 0.5-2h; the hydrothermal reaction temperature is 120-180°C, preferably 170°C; the hydrothermal reaction time is 6-36h, preferably 24h.

5. The method for preparing a catalyst according to claim 2, characterized in that: In step 3, the carbon thermal reduction temperature under nitrogen atmosphere is 500-800° C., and the reaction time is 0.5-4 h.

6. A method for using any one of the amorphous carbon layers described in claims 1 to 5 to encapsulate a non-precious metal-loaded nitrogen-doped mesoporous carbon catalyst (M-NCG) in the efficient catalysis of levulinic acid hydrogenation to prepare γ-valerolactone.

7. The method according to claim 6, characterized in that: With hydrogen as hydrogen source, catalyst, solvent and levulinic acid are placed in a polytetrafluoroethylene lined reactor for stirring and reaction to obtain the product γ-valerolactone, the reaction temperature is 140-200°C, the reaction time is 1-10h, and the hydrogen pressure is 1-2MPa.

8. The method according to claim 7, characterized in that: The solvent is one of 1,4-dioxane, ethanol, methanol and isopropanol, preferably 1,4-dioxane; the mass ratio of levulinic acid to the catalyst in the reaction system is (3-20):1.

Citation Information

Patent Citations

  • A method for the hydrogenation of levulinic acid to γ-valerol using a ruthenium catalyst supported on a sulfur-doped carbon material.

    CN108409692B

  • A noble metal single-atom catalyst and its preparation method using notched polyacid assistance.

    CN111841611B

  • A cobalt-nitrogen co-doped fish scale biochar catalyst, its preparation method and application

    CN113546664B

  • Cobalt single-atom / nitrogen-doped mesoporous carbon fiber materials, their preparation methods and applications

    CN114308094B